Thalāth Marāhil li-Tatwīr Ta'līm al-Lughah al-'Arabiyah fī Indūnīsiyā (Dirāsah Tārīkhiyah wa Minhājīyah) - Muhajir (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
The spread of Islam in Indonesia is closely related to the activity of Arabic language learning. As a code of linguistic expressions in learning Islam, the first aim in learning Arabic language in Indonesia is to fulfill people’s need in praying. In the second phase, Arabic language learning developed at many Islamic Boarding Schools. There was awareness that Arabic language was not only a tool in understanding a text, but also a tool for communication. It makes many people, especially those who studied abroad in the Middle East, motivated to innovate in the education development such as finding new concept and new teaching method especially in Arabic language teaching. In the third phase, Arabic language learning is nowadays used in a formal education and it is still in the process of completion of its curriculum, learning objective, learning material, teaching method, and its teaching media used in the teaching and learning process.